1997
DOI: 10.1093/humrep/12.8.1720
|View full text |Cite
|
Sign up to set email alerts
|

Successful induction of ovulation in normogonadotrophic clomiphene resistant anovulatory women by combined naltrexone and clomiphene citrate treatment

Abstract: Patients suffering from normogonadotrophic anovulation and infertility are initially treated with clomiphene citrate. Those who do not respond to clomiphene citrate usually receive gonadotrophin treatment which is labour-intensive, expensive, and associated with an increased risk of multiple pregnancies and ovarian hyperstimulation syndrome. We treated 22 patients with clomiphene resistant normogonadotrophic anovulation with naltrexone (an opioid receptor blocker) alone or naltrexone in combination with an ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The increase in LH pulse amplitudes persisted over the entire duration of treatment of 6 months (47) or up to 630 days (11). Even in patients suffering from anovulatory cycles, higher ovulation rates resulted after treatment with naltrexone or naltrexone in combination with clomiphene, versus clomiphene alone (48). After a treatment course of 9 months with daily naltrexone doses of 50-150 mg, Wildt et al reported a per-cycle pregnancy rate of 29% (25).…”
Section: Hypothalamic Amenorrheamentioning
confidence: 99%
“…The increase in LH pulse amplitudes persisted over the entire duration of treatment of 6 months (47) or up to 630 days (11). Even in patients suffering from anovulatory cycles, higher ovulation rates resulted after treatment with naltrexone or naltrexone in combination with clomiphene, versus clomiphene alone (48). After a treatment course of 9 months with daily naltrexone doses of 50-150 mg, Wildt et al reported a per-cycle pregnancy rate of 29% (25).…”
Section: Hypothalamic Amenorrheamentioning
confidence: 99%
“…A great deal of evidences indicate that hyperinsulinemia, abnormal LH secretion and opioid tone may have a key role in pathophysiologic mechanisms responsible for chronic anovulation in PCOS patients [17,59,60]. Recently we tried to verify whether the benefits of naltrexone in these women could be applied to the clinical management of their infertility [61].…”
Section: Naltrexone Treatment: Implications For the Management Of Pcomentioning
confidence: 99%
“…Nevertheless, when clomiphene is given to properly selected women with no other causes of infertility apart from anovulation, cumulative pregnancy rates of Ͼ60% after 6 months and Ͼ90% after 10-12 months have been reported (Hammond et al, 1983;Messinis and Milingos, 1997). Combinations of clomiphene with other drugs, such as naltrexone, in clomiphene resistant patients are also successful (Messinis and Milingos, 1997;Roozenburg et al, 1997). The low risk of the ovarian hyperstimulation syndrome (OHSS) and the low rate of multiple pregnancy during treatment with clomiphene makes it the safest way of treating anovulatory infertility in women belonging to WHO 2363 group II.…”
Section: Monofollicular Developmentmentioning
confidence: 99%